Partículas magnéticas: síntese e aplicações em ensaios de 3 imunoseparação - Monte, Leonardo Garcia (2011)
The development of reagents for infectious disease diagnosis and prevention is strategic for the scientific and technological advance of the country. Promising results have been obtained with the use of magnetic nanocomposites (MNC) in health for several purposes as separation, purification and detection of cells or biomolecules. In this work, an immunomagnetic separation (IMS) method using carbon and cobalt-based (MNCc), synthesized, and other polystyrene and iron-based (MNCp) commercially available was applied, for the isolation and detection of pathogenic leptospires. The MNCc were synthesized through polymeric precursor method and characterized by scanning electron microscopy/transmission (SEM/TEM), X-ray diffractometry (XRD), infrared spectrometry (FTIR), and immunofluorescence (IF). The MNCc surface was functionalized with carboxylic groups through the incorporation of acrylic acid. MNCc, adsorbed with monoclonal antibodies (MAbs) against pathogenic leptospires, were used in the IMS assays followed by PCR and cell culture was able to detect and isolate the organism. MNCp were used for detecting Leptospira spp. in biological fluids from dogs artificially contaminated with leptospires, and clinical samples from dogs positive for leptospirosis. The introduction of IMS, as a step prior to PCR using MNCp, detected a concentration of leptospires ten times smaller when compared to PCR performed directly on artificially contaminated urine and blood samples. Moreover, the IMS performed with MNCp increased PCR sensitivity in clinical samples from dogs positive for leptospirosis. Data from both studies suggest that MNCc and MNCp are important tools for the development of new diagnosis tests.